Inventions for SARS-CoV-2 vaccines - Lefakis (Λέανδρος Λεφάκης), Leandros (Bioethica, 2020)
The rapid spread of the SARS-CoV-2 virus is the new pandemic that humanity is called upon to deal with. The special characteristics of the virus in combination with the absence of effective antiviral medication and vaccine, make the disease a significant threat to global health. This paper addresses the issue of innovation in the midst of a pandemic in the field of diagnostic and therapeutic procedures, namely vaccines for the SARS-CoV-2 virus and how these could become public goods that will be provided without expected profit, considered global public goods. The issue is so crucial for public health that the State and the international community are called upon to contribute to research and development, in terms of participating in the business risk of the industry (with public funding), but also to intervene to protection of the global good of public health, possibly considering compulsory patent licensing solutions that will result from vaccine research.